The discourse of men's facial care products in Instagram from the Foucauldian perspective - Putranto, Teguh Dwi; Suyanto, Bagong; Ariadi, Septi; Santos, Roberto Rudolf T. (Jurnal Studi Komunikasi, 2021)
Talking about body appearance, of course, cannot be separated from metrosexual men who tend to place great importance on appearance, from the way of dress to rituals in caring for their bodies. The men's body has been viewed and utilised as a commodity from the capitalist industry to rival the women's body. This study seeks to explore the discourse Erto's Men as one of facial care product for men built through posts on Instagram because Erto's Men is the face care product that appears the most in searches via #metrosexual on Instagram. The method used in this research is a critical discourse analysis on the @ertosmen Instagram post from June until August 2020. The results obtained in this study indicate that Erto's Men as a men facial skincare product builds a disciplining men's bodies by juxtaposing metrosexual representations through clean and bright skin, and with masculine representations through beard growth. So that through this representation, Erto's Men also helps build a health discourse for men through masculine concepts.